Effects of zoledronate versus placebo on spine bone mineral density and microarchitecture assessed by the trabecular bone score in postmenopausal women with osteoporosis: A three‐year study. (15th February 2013) - Popp, Albrecht W; Guler, Sabina; Lamy, Olivier; Senn, Christoph; Buffat, Helene; Perrelet, Romain; Hans, Didier; Lippuner, Kurt
Abstract: The trabecular bone score (TBS) is an index of bone microarchitectural texture calculated from anteroposterior dual‐energy X‐ray absorptiometry (DXA) scans of the lumbar spine (LS) that predicts fracture risk, independent of bone mineral density (BMD). The aim of this study was to compare the effects of yearly intravenous zoledronate (ZOL) versus placebo (PLB) on LS BMD and TBS in postmenopausal women with osteoporosis. Changes in TBS were assessed in the subset of 107 patients recruited at the Department of Osteoporosis of the University Hospital of Berne, Switzerland, who were included in the HORIZON trial. All subjects received adequate calcium and vitamin D3. In these patients randomly assigned to either ZOL ( n = 54) or PLB ( n = 53) for 3 years, BMD was measured by DXA and TBS assessed by TBS iNsight (v1.9) at baseline and 6, 12, 24, and 36 months after treatment initiation. Baseline characteristics (mean ± SD) were similar between groups in terms of age, 76.8 ± 5.0 years; body mass index (BMI), 24.5 ± 3.6 kg/m 2 ; TBS, 1.178 ± 0.1 but for LS T ‐score (ZOL–2.9 ± 1.5 versus PLB–2.1 ± 1.5). Changes in LS BMD were significantly greater with ZOL than with PLB at all time points ( p < 0.0001 for all), reaching +9.58% versus +1.38% at month 36. Change in TBS was significantly greater with ZOL than with PLB as of month 24, reaching +1.41 versus–0.49% at month 36; p = 0.031, respectively. LS BMD and TBS were weakly correlated ( r = 0.20) and there were no correlations between changes in BMD and TBS from baseline at any visit. In postmenopausal women with osteoporosis, once‐yearly intravenous ZOL therapy significantly increased LS BMD relative to PLB over 3 years and TBS as of 2 years. © 2013 American Society for Bone and Mineral Research.